SISTEM INFORMASI PENGOLAHAN DATA TERNAK UNIT PELAKSANA TEKNIS PRODUKSI DAN KESEHATAN HEWAN BERBASIS WEB - Nawassyarif; M. Julkarnain; Kiki Rizki Ananda (Program Studi Informatika Universitas Teknologi Sumbawa, 2020)
The processing data is process of input and output data become another form that very needed which is the special information of livestock processing data. The unit of implementation technical production and health of animal (Prokeswan) Lape sudistrict and Lopok subdistrict as one of a government service that have various type of affairs, like like the processing data of livestock that cover the result of registration of livestock data and a mutation data of livestock. A livestock data collection is activities that carried out by subdistrict officials to know the number of livestock in every village. Research items to design and build information system processing of livestock in information of livestock processing data. The unit of implementation technical production and health of animal (Prokeswan) lape subdistrict and Lopok subdistrict in Web-based. The system was developed using the PHP language programming and using MySql as a database. The method of the developed of this software using waterfall method. The testing of this software through Black Box testing that is testing that do with testing the software in functional terms. The instruments Technic Collecting data in this research using interview and literature review. The final result of research is design and build an information system processing of livestock data Web-based can facilitate officer and employer to processing livestock data, this system also can speed up saving data, processing, collecting and display data to produce the quality information and also processing the data become a report that able to present the complete livestock data of UPT Prokeswan Lape subdistrict and Lopok subdistrict.